A rare cause of glans penis masses in childhood: Fibroepithelial polyp - Arzu Sencan; Aydin Sencan; Cuneyt Gunsar; Hasan Cayirli; Nalan Nese (Wolters Kluwer Medknow Publications, 2015)
Fibroepithelial polyps of glans penis are very rarely seen in childhood. A 6-month-old male admitted to our institution with a slowly enlarging glans penis mass on the ventral side of the glans penis. The mass was totally excised, and hystopathological diagnosis was a fibroepithelial polyp. All of the reported cases published previously, except one, are of adult age and all of them have been associated with the history of long-term condom catheter use. The presence of the case in childhood; however, suggests that the pathology might be congenital. This is the second pediatric case presented in the English literature.